2017
DOI: 10.1107/s2056989017001177
|View full text |Cite
|
Sign up to set email alerts
|

Four pyrrole derivatives used as building blocks in the synthesis of minor-groove binders

Abstract: The title nitro­pyrrole-based compounds are inter­mediates used in the synthesis of modified DNA minor-groove binders. They are ethyl 4-nitro-1H-pyrrole-2-carboxyl­ate, its derivative ethyl 4-nitro-1-(4-pentyn­yl)-1H-pyrrole-2-carboxyl­ate, N-[3-(di­methyl­amino)­prop­yl]-1-isopentyl-4-nitro-1H-pyrrole-2-carboxamide and 1-(3-azido­prop­yl)-4-(1-methyl-4-nitro-1H-pyrrole-2-carboxamido)-N-[2-(morpholin-4-yl)eth­yl]-1H-pyrrole-2-carboxamide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Suckling et al have recently reported four nitro­pyrrole-based compounds (conjugates 44 – 47 , Fig. 9 ) as building blocks for the synthesis of novel minor groove binders [ 110 ]. Crystal structure data revealed that nitro groups and ester moieties in conjugates 44 and 45 are coplanar with the pyrrole ring, whereas the isopropyl fragment in conjugate 46 lies out of the pyrrole plane.…”
Section: Reviewmentioning
confidence: 99%
“…Suckling et al have recently reported four nitro­pyrrole-based compounds (conjugates 44 – 47 , Fig. 9 ) as building blocks for the synthesis of novel minor groove binders [ 110 ]. Crystal structure data revealed that nitro groups and ester moieties in conjugates 44 and 45 are coplanar with the pyrrole ring, whereas the isopropyl fragment in conjugate 46 lies out of the pyrrole plane.…”
Section: Reviewmentioning
confidence: 99%